Global patterns and drivers of coupling between anammox and denitrification processes across inland aquatic ecosystems - Xiaoguang Xu; Yuxuan Yang; Yiwen Zhou; Jie Ma; Jining Li; Xiaohong Zhou; Xiaoli Zhao; Fengchang Wu; Kang Song (Communications Earth & Environment)
Abstract Denitrification and anammox collectively drive nitrogen loss from aquatic ecosystems, yet their global patterns and interactions remain unclear. To fill this gap in knowledge, we compiled a global dataset on anammox and denitrification, encompassing river, lake, wetland, and estuary ecosystems and comprising 2539 observations from 136 peer-reviewed papers. Here, we show that aquatic ecosystems with abundant denitrifying bacteria tend to have abundant anammox bacteria, but the abundance of anammox bacteria is lower than that of denitrifying bacteria. Importantly, we observed that hotspots for denitrification in aquatic ecosystems were also hotspots for anammox, and we explained the variation in anammox (21.55 (95% CI: 8.21–58.90) nmol-N g-1 day-1) and denitrification rates (171.76 (95% CI: 65.40–519.25) nmol-N g-1 day-1) across aquatic ecosystems. These results highlight that anammox should be included in models for accurate nitrogen budget assessment in aquatic ecosystems on a global scale, especially in the context of future climate warming.